WHAT UNIVERSITY-STUDENTS BELIEVE ABOUT PLAGIARISM - Nimasari, Elok Putri; Gestanti, Rohfin Andria; Mufanti, Restu (PEOPLE: International Journal of Social Sciences, 2019)
Plagiarism among academicians has been a popular issue in Indonesia for the last five years. Some people argue that plagiarism occurs due to pressure of work to get certain level of academic degree. Another opinion claims that it is due to incapability of writing an academic paper. Plagiarism is definitely unacceptable and not tolerated in any context. Writing an academic paper is about producing a masterpiece. An academic writing should be given a high appreciation to boost positive motivation for academicians to write and publish their research papers. A lot of efforts have been conducted by institutions to avoid plagiarism, such as giving academic writing lectures and citation training, and checking papers using plagiarism checker tools. However, plagiarism still has its popularity among academicians including students and lecturers. For this reason, it is interested to study how those academicians perceive plagiarism. We specify the study by subjecting the research for university student. We investigate students’ behavior towards plagiarism. Thirty-five students of a private university in Ponorogo, Indonesia are purposively taken as sample of the study and they are interviewed to gain the data. The results of data analysis are discussed with related literatures to draw the conclusions.